IMPLEMENTATION OF PEER TUTORING METHOD IN PAI LEARNING PROCESS TO IMPROVE STUDENTS' LEARNING MOTIVATION AT STATE SENIOR HIGH SCHOOL 1 SETIA BAKTI - Lely farah (CV. Asry Persada Quality, 2025)
The above research focuses on the planning, implementation and results of Peer Tutor method in the learning process of Islamic Religious Education at SMA Negeri 1 Setia Bakti Senior High School. This is indicated by the quality of education in the country which has not been able to compete at the international level. One of the reasons is the use of innovative learning strategies from educators has not been optimal. The existence of this peer tutoring method is very helpful in protecting students who feel less capable of PAI subjects. Peer tutoring by peers can eliminate awkwardness, yes, language friends are easier to understand, besides that with peers there is no feeling of hesitation, humility and shame to ask or ask for help. The conclusions of this study include: (1) The planning of the peer tutoring method in the learning process of Islamic Religious Education at SMA Negeri 1 Setia Bakti was prepared carefully (2) The implementation of the Peer Tutor method in the learning process of Islamic Religious Education at SMA Negeri 1 Setia Bakti has run optimally (3) The results of the application of the Peer Tutor method in the PAI learning process on motivated students at SMA Negeri 1 Setia Bakti are good.